Distribuição intragástrica de refeição e esvaziamento gástrico na dispepsia funcional: uma análise multissegmentar - Ietsugu, Marjorie do Val [UNESP] (2015)
Gastrointestinal motility abnormalities are involved in the etiology of functional dyspepsia (FD), which is characterized by several manifestations with no organic disease that explain the symptoms; it fits into the functional gastrointestinal disorders. Scintigraphy is the gold standard technique to FD assessment; however there is no standard application for evaluate gastric motility alterations. The aim of this study was to evaluate, by scintigraphy, gastric total emptying (GE), regional and intragastric distribution of meal (IDM) using two segmentations and to assess frequency and amplitude of contractions in proposed segmentations in dyspepsia by dynamic scintigraphic. Thirty four individuals, 20 normal and 14 dyspeptics were evaluated, selected according to Rome III. The test meal and protocols of static images acquisition obtained immediately and at intervals of 60, 120 and 240 minutes after ingestion of the test meal were recommended by consensus; in addition, dynamic images of 1 Hz were acquired after immediate image and before image referent to 60 minutes of ingestion. Data were analyzed in MatLab® with images segmentation in proximal and distal regions. Total GE in dyspepsia was similar to normal individuals. However, the regional GE and the IMD were altered in dyspepsia, independently of segmentation, indicating GE should be evaluated not only by the test meal retention, but also considering classical parameters and visual image analysis. Dynamic acquisition in associated with statics images represented a tool to measure regional GE, allowing quantification of the IMD and dominant frequencies (DF) and amplitudes of regional gastric contractions. Differences between groups were observed independently of segmentation, encouraging the use of segmentation according to half of gastric area due to minor proximal regional influence. Although DF hasn't differed in both regions between groups, smaller amplitude of contraction ...